Effect of different doses of Ovaprim (sGnRHa+Domperidone) on the eGG fecundity and REPRODUCTIVE HORMONE LEVELS IN Channa marulius - M. Hafeez-ur-Rehman; M. Ashraf; F. Abbas; I. A. Qureshi; M. Mehmood-ul-Hassan; K. J. Iqbal; S. Abbas (Journal of Animal and Plant Sciences, 2015)
The study was conducted to determine the efficacy of various doses of Ovaprim on reproductive behavior of Channa marulius. Fish was fed on 40% protein containing diet at 5% of its body weight for 4 months. On maturity, males weighed were 1100-1340 g and females 1150-1350 g.  Two males and two females were randomly paired (8 pairs in total), the 4 groups which emerged were names as control, treatment 1, 2 and 3 (each in 2 replicate tanks). Each male and female received Ovaprim intramuscularly in two installments with an interval of 24 hours.  The blood samples were drawn from each sex with an interval of 2 hour for estimation of testosterone, FSH and LH levels. None of the fish spawned even after 48 hours of hormone administration. Ovaries were removed from each fish, weighed and eggs were counted. Fecundity (No.of eggs) was 870.0 ±75.27, 811.2 ±103.30, 900.0 ±95.56 and 940.0 ±39.79 in Control, T1, T2, and T3 respectively. Mean ova diameter ranged from 1.48±0.02 to 1.54±0.01mm. The lowest mean ova diameter (1.48±0.02 mm) was observed in control tank (0.4 ml Ovaprim/kg b.w) while the highest (1.54±0.01 mm) was in T1 (0.5ml Ovaprim/kg b.w.). The highest testosterone level (2.05±0.11 ng ml-1) was observed in T3 after 20 hours of first injection of Ovaprim while the highest FSH level (0.88±0.02 ng ml-1) was observed in the same treatement after the 28 hours of hormone injection. These studies discovered that Ovaprim dosages are inadequate for stimulation of breeding.
Keywords: Ovaprim; hormone; fecundity; blood chemistry; Channa marulius